Pengucapan ‘Selamat Natal’ Oleh Umat Islam Kepada Umat Kristiani Perspektif Filsafat Hukum Islam - Harianto, Bobby (QIYAS: JURNAL HUKUM ISLAM DAN PERADILAN, 2016)
Abstract: Greeting Of ‘Merry Christmas’ By Muslims To Christians In Islamic Perspective. The greeting of ‘Merry Christmas’ is usually pronounced when the Christian welcome the birth of Jesus. In Indonesia, there are still differences of opinion on whether or not allowed for Muslims to say ‘Merry Christmas’ to Christians as a form of respect and tolerance for the Christians. Some ulema are strictly prohibiting to greet Christian by saying ‘Merry Chirstmas’ because this act is a part of religious rituals, and others allow it with certain terms and conditions. To clarify the Islamic legal regarding the greeting of ‘Merry christmas’, this article will explore more deeply through a review of the philosophy of Islamic law. This study is a qualitative research approach. In general there are two approaches that will be used by the researchers, namely: a phenomenological approach and a juridical philosopy approach. In the mean time, the researcher also used the conceptual approach, case approach, as well as comparative approach. The research shows that greeting by saying ‘Merry Christmas’ to Christian is considered as haram li dzatihi (prohibited) because faith related issues. The prohibitation applies as long as not in the state of urgent or special needs.